Incorporating memory effects in phase separation processes - Koide, T.; Krein, G.; Ramos, R. O. (Elsevier B.V., 2006)
We consider the modification of the Cahn-Hilliard equation when a time delay process through a memory function is taken into account. We then study the process of spinodal decomposition in fast phase transitions associated with a conserved order parameter. Finite-time memory effects are seen to affect the dynamics of phase transition at short times and have the effect of delaying, in a significant way, the process of rapid growth of the order parameter that follows a quench into the spinodal region. These effects are important in several systems characterized by fast processes, like non-equilibrium dynamics in the early universe and in relativistic heavy-ion collisions. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: non-equilibrium field dynamics; memory effects; relativistic heavy-ion collisions